Multiparametric magnetic resonance-guided and monitored microwave ablation in liver cancer - Zhang Kai; Liu Ming; Xu Yu J; He Xiang M; Sequeiros Roberto B; Li Cheng L (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2022)
Purpose: The objective of our study was to prospectively evaluate the feasibility, effectiveness, and safety of 1.0T open multiparametric magnetic resonance (MR)-guided and monitored microwave ablation (MWA) of liver cancer. Materials and Methods: Fifty-six liver lesions (12 - initial hepatocellular carcinoma, 34 - recurrent hepatocellular carcinoma, and 10 - metastatic liver cancers) in 45 patients were treated with MWA ablation using MR guidance and monitoring. The mean diameter of the liver lesions was 1.7 +/- 0.9 cm (range, 0.5-4.6 cm). The 56 liver lesions were divided into 3 groups according to diameter: the <1.0 cm group (17 lesions), the 1.0-2.0 cm group (19 lesions), and the >2.0 cm group (20 lesions). Technical success, technical effectiveness, local tumor progression, procedure duration, and complications were assessed. Primary technical effectiveness was assessed 3 months after the MWA, while local tumor progression was assessed more than 3 months after the MWA. The follow-up time for assessment of treatment response ranged from 12 to 30 months (median, 23 months).
Results: The technical success rate was 100%. Primary technical effectiveness was achieved in 52/56 (92.8%) lesions. Local tumor progression was detected in three tumors after initial technical effectiveness. The median duration of the intervention per tumor was 66 min (range, 40-156 min). There were no significant differences between lesion groups in the technical success rate, primary technical effectiveness rate, or local tumor progression rate. There were no major complications following the ablation therapy.
Conclusions: 1.0T open multiparametric MR-guided and MR-monitored MWA for liver cancer is safe and feasible and decreases the risk of local tumor progression; it also provides good primary technique effectiveness rates and is especially suitable when ultrasound and CT facilitated treatments are inappropriate.